Jealousy due to social media? A systematic literature review and framework of social media-induced jealousy - Tandon Anushree; Dhir Amandeep; Mäntymäki Matti (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose The association between social media and jealousy is an aspect of the dark side of social media that has garnered significant attention in the past decade. However, the understanding of this association is fragmented and needs to be assimilated to provide scholars with an overview of the current boundaries of knowledge in this area. This systematic literature review (SLR) aims to fulfill this need.
Design/methodology/approach The authors undertake an SLR to assimilate the current knowledge regarding the association between social media and jealousy, and they examine the phenomenon of social media-induced jealousy (SoMJ). Forty-five empirical studies are curated and analyzed using stringent protocols to elucidate the existing research profile and thematic research areas.
Findings The research themes emerging from the SLR are (1) the need for a theoretical and methodological grounding of the concept, (2) the sociodemographic differences in SoMJ experiences, (3) the antecedents of SoMJ (individual, partner, rival and platform affordances) and (4) the positive and negative consequences of SoMJ. Conceptual and methodological improvements are needed to undertake a temporal and cross-cultural investigation of factors that may affect SoMJ and acceptable thresholds for social media behavior across different user cohorts. This study also identifies the need to expand current research boundaries by developing new methodologies and focusing on under-investigated variables.
Originality/value The study may assist in the development of practical measures to raise awareness about the adverse consequences of SoMJ, such as intimate partner violence and cyberstalking.